From Sensitivity to Tolerance – A Homeopathic Perspective on Restoring Immune Balance in Food Allergies (Homoeopathy for All, 2026)
Food allergy is an increasingly  prevalent immunological disorder,  particularly affecting children and  young adults, where the burden  is both clinically significant and  rising. Recent epidemiological  data indicate that food allergy  affects approximately 6–8% of  children under 5 years and nearly  4–5% of older children and  adolescents, with persistence into  adulthood observed in a substantial  proportion of cases. In young  adults, prevalence estimates range  between 3–4%, often representing  either persistent childhood allergies  or newly developed sensitivities.  Notably, studies suggest that over  the past two decades, there has  been a two- to three-fold increase  in pediatric food allergy cases  globally, with similar upward trends  reported in urban populations and  developing countries, including  India. This rise has been attributed  to factors such as altered dietary  habits, reduced microbial exposure  (hygiene hypothesis), environmental  pollution, and early-life gut  microbiome disturbances. At the  mechanistic level, food allergy is  primarily associated with the loss  of oral tolerance a highly regulated  immunological process by which  the gastrointestinal immune system  learns to recognize and remain  unresponsive to harmless food  proteins. This tolerance is mediated  by complex interactions involving  gut-associated lymphoid tissue  (GALT), antigen-presenting cells,  and regulatory T cells (Tregs), which  actively suppress hypersensitivity  reactions. Such intolerances have  been observed with foods containing  soy, gluten, nuts, and others.
Keywords: epidemiological data; developed sensitivities; hygiene hypothesis; hypersensitivity reactions